Status and contamination level of water quality in Lake Chini, Malaysia - Arafat, Md. Yasir; Islam, Mir Sujaul; Mohamad Idris, Ali; Zularisam, A. W. (Universiti Malaysia Pahang, 2016)
The study investigates the spatial variation and index of water quality in Tasik Chini (Chini Lake), Pahang, Malaysia. Water sampling was conducted from 15 representative sites within the lake including five major feeder rivers. Major physico-chemical indicators of water quality were analyzed using standard procedures. Observed research data were calculated according to Department of Environment Water Quality Index (DOE-WQI) and classified in comparison with National Water Quality Standard, Malaysia (NWQS). pH and ammoniacal nitrogen were most polluted parameter in the study area. Station T4 was worse in condition (class III) where tributaries were mostly polluted followed by agriculture and mining area at station L3 and L4. The lake water quality was classified as class II based on WQI Malaysia. That is quite suitable for body contact and recreational purpose.